Nomenclatural bingo for the beans to go: A revised classification of Fabodae (Fabaceae: Papilionoideae) - Jiang, Kai-Wen; Feng, Zhen-Hao; Liu, Bing; Liu, Su (Phytotaxa, 2025)
Based on recent advances in phylogenetic studies of the Fabaceae, a novel suprageneric classification is proposed for one of its supertribes, incorporating significant redelimitations at tribal and subtribal levels. The supertribe Galegodae is herein replaced by Fabodae, which comprises 12 tribes. A new tribe, Schefflerodreae, is proposed and the tribe Fabeae is recircumscribed to include seven subtribes, with Fabinae established as a novelty, encompassing seven genera. Additional remarks on these tribes, subtribes and genera in need of clarifications are provided. Furthermore, updated keys for the tribes of Fabodae, the subtribes of Fabeae, and the genera of Fabinae are presented.